PROSES PENYITAAN BARANG BUKTI DALAM TINDAK PIDANA PENCURIAN SEPEDA MOTOR (Studi Polrestabes Makassar) - Ardia Uga Marwani; Mulyati Pawenai; Dachran Bustami (Qawanin Jurnal Ilmu Hukum, 2020)
The research objectives were to determine the implementation of the authority of investigators in confiscating evidence of motorcycle theft, and to determine the obstacles experienced by investigators in confiscating evidence of motorcycle theft. This research is empirical, which is research based on facts in society regarding the factors that lead to the crime of motorbike theft and the process of confiscating evidence in the crime of motorcycle theft. The results of this study illustrate that in carrying out the confiscation of evidence of motorcycle theft, there are obstacles experienced by investigators, namely when confiscating items that have been dissected and in confiscating evidence of motorcycle theft that has been sold outside the investigator's jurisdiction. The Criminal Procedure Code does not regulate confiscation outside the jurisdiction of an investigator. As a suggestion, it is necessary to make clearer and more detailed provisions regarding the accountability mechanism of the party who is physically responsible for the confiscated objects, in this case there is a loss or a form of deterioration in the quality of the confiscated objects.